Immunohistochemical localization of irisin in mole rats (Spalax leucodon) - Gur, F. M.; Timurkaan, S.; Yalcin, M. H.; Girgin, A.; Tarakci, B. Gencer (Taylor & Francis Inc, 2017)
Irisin was first identified in skeletal muscle cells. It is an exercise protein that is secreted into the circulation; it causes conversion of white adipose tissue to brown adipose tissue. We investigated irisin immunoreactivity in mole rat (Spalax leucodon) tissues. We examined cerebellum, pituitary, heart, liver, pancreas, spleen, uterus, kidney and striated muscle in female adult mole rats. Tissues were processed, embedded in paraffin, sectioned at 5 m and stained immunohistochemically for irisin. Irisin immunostaining was detected in the cytoplasm of stained cells; the cytoplasm of Purkinje cells was unstained. We found that irisin may be synthesized in many tissues. The function of locally synthesized irisin currently is unknown.
Keywords: cerebellum; heart; immunohistochemistry; irisin; kidney; liver; mole rats; pancreas; pituitary; Spalax leucodon